2006
DOI: 10.1021/ja0578698
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Interference with N-Acyl Homoserine Lactone-Mediated Bacterial Quorum Sensing

Abstract: Cell density-dependent coordination of gene expression in bacteria has been termed "quorum sensing" (QS). 1 N-acyl L-homoserine lactones (AHLs) are produced by over 70 species of Gram-negative bacteria, and structural differences within AHLs occur in the length and oxidation state of the acyl side chain (Figure 1). Upon reaching a critical threshold concentration, AHLs bind to their cognate receptor proteins, triggering the expression of target genes. AHLs have been shown to play an important role in the estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 19 publications
3
89
0
Order By: Relevance
“…In order to overcome the small size of AHLs and to potentiate the maximal response for antibody generation, Janda and coworkers (104) pioneered a study where AHLs and AHL analogues were chemically conjugated to keyhole limpet hemocyanin (KLH) or bovine serum albumin (BSA), leading to efficient production of AHL-sequestering antibodies. These antibodies have shown very promising efficacy in protecting mice against P. aeruginosa infections (103,104,135).…”
Section: Targeting Bacterial Signalingmentioning
confidence: 99%
“…In order to overcome the small size of AHLs and to potentiate the maximal response for antibody generation, Janda and coworkers (104) pioneered a study where AHLs and AHL analogues were chemically conjugated to keyhole limpet hemocyanin (KLH) or bovine serum albumin (BSA), leading to efficient production of AHL-sequestering antibodies. These antibodies have shown very promising efficacy in protecting mice against P. aeruginosa infections (103,104,135).…”
Section: Targeting Bacterial Signalingmentioning
confidence: 99%
“…The development of monoclonal antibodies (MAbs) against AHLs was first achieved using lactam-containing haptens whose linkers mimicked naturally occurring AHL acyl chains of various lengths and oxidation states (109). The highest-affinity MAbs were specific for 3OC12HSL, and investigators were able to demonstrate that one of these MAbs, RS2-1G9, inhibited QS signaling and QS-regulated pyocyanin production in P. aeruginosa in vitro, suggesting therapeutic potential of antibody-mediated QSI (109).…”
Section: Nonenzymatic Inactivation and Sequestration Of Qs Signals Usmentioning
confidence: 99%
“…The development of monoclonal antibodies (MAbs) against AHLs was first achieved using lactam-containing haptens whose linkers mimicked naturally occurring AHL acyl chains of various lengths and oxidation states (109). The highest-affinity MAbs were specific for 3OC12HSL, and investigators were able to demonstrate that one of these MAbs, RS2-1G9, inhibited QS signaling and QS-regulated pyocyanin production in P. aeruginosa in vitro, suggesting therapeutic potential of antibody-mediated QSI (109). Shortly thereafter, Miyairi and colleagues demonstrated that active immunization with bovine serum albumin (BSA)-conjugated 3OC12HSL increased survival of mice following intranasal challenge with P. aeruginosa, despite having no effect on bacterial burdens in the lung (110).…”
Section: Nonenzymatic Inactivation and Sequestration Of Qs Signals Usmentioning
confidence: 99%
“…Furthermore, existing monoclonal antibodies show little or no cross-reactivity with related HSL compounds (13). Antibodies that cross-react with C 4 -HSL would provide an added therapeutic advantage as they may also prevent the establishment of rhl QS system effects in the absence of the las system.…”
mentioning
confidence: 99%